The Determinants of Bank Profitability in China from 2012 to 2017 - Yu, Binfeng (2017)
The banking reforms in China over the past 20 years (1997-2017) were aimed at increasing the competitive power of banks, their profitability and enhancing the stability of the banking sector. Despite the fact that various researchers thoroughly scrutinised determinants of profitability, the evidence available in scientific journals is often outdated. The research attempts to bridge the gap in existing studies and provide an updated review of the subject. The analysis significantly contributes to the existing empirical literature by assessing the impact of individual banks’ characteristics, macroeconomic variables and ownership forms on profitability of Chinese banks. For that purpose, the Fixed Effects model and the Random Effects model are constructed. The performance of banking sector is observed over the period of five years (2012-2016). The results show that relationships between banks’ characteristics such as Costs to Income ratio and Total Equity to Total Assets ratio and profitability ratios such as Return on Assets and Return on Equity are negative and significant. Considering macroeconomic variables, the evidence is mixed. Finally, ownership forms are found to have no impact on profitability measures. The research provides policy recommendations to the Chinese banking sector and managers of individual banks.